Access to medicines for acute illness in middle income countries in Central America - Isabel Cristina Martins Emmerick; Vera Lucia Luiza; Luiz Antonio Bastos Camacho; Dennis Ross-Degnan (Universidade de São Paulo, 2013)
OBJECTIVE : To analyze the main predictors of access to medicines for persons who experienced acute health conditions. METHODS : This was a cross-sectional analytic study, based on data from household surveys. We examined the predictors of: (1) seeking care for acute illness in the formal health care system and (2) obtaining all medicines sought for the acute condition. RESULTS : The significant predictors of seeking health care for acute illnesses were urban geographic location, head of household with secondary school education or above, age under 15, severity of illness perceived by the respondent, and having health insurance. The most important predictor of obtaining full access to medicines was seeking care in the formal health care system. People who sought care in the formal system were three times more likely to receive all the medicines sought (OR 3.0, 95%CI 2.3;4.0). For those who sought care in the formal health system, the strongest predictors of full access to medicines were seeking care in the private sector, having secondary school education or above, and positive perceptions of quality of health care and medicines in public sector health facilities. For patients who did not seek care in the formal health system, full access to medicines was more likely in Honduras or Nicaragua than in Guatemala. Urban geographic location, higher economic status, and male gender were also significant predictors. CONCLUSIONS : A substantial part of the population in these three countries sought and obtained medicines outside of the formal health care system, which may compromise quality of care and pose a risk to patients. Determinants of full access to medicines inside and outside the formal health care system differ, and thus may require different strategies to improve access to medicines.